SERAT WEDATAMA AND CHARACTER EDUCATION - HY Agus Murdiyastomo (Journal of Social Studies (JSS), 2017)
Many people understand that a character education is only related to politeness. This understanding is certainly too narrow because character in Javanese culture has broader meaning than just being polite. The ideas regarding character education have been presented by Mangkunegara IV through his work of Serat Wedatama. Problems arise when the work is written in the form of symbolic traditional songs, namely Pangkur, Sinom, Pocung, and gambuh. This paper aims at investigating the kinds of character messages presented in the first section of Serat Wedatama which was composed in the form of pangkur traditional songs. The method employed in this research is a historical research method, whose stages include heuristics, criticism, interpretation, and historiography. Considering the object of the study is a manuscript, content analysis and semantic approaches are utilized. The approach was chosen merely to obtain the clarity of the meaning which are implicitly expressed in the form a traditional song of pangkur. The results are traditional songs describes the atmosphere, circumstances, or will to be achieved. The first section of pangkur traditional song, in general, contains a message about the guidance to achieve the perfection of which can be attained by abandoning worldly things. Among the 14 traditional songs of Pangkur, their first section presents some basic thoughts namely Angkara, Ngelmu, Atining Tatakrama, Lumuh asor kudu unggul, puruhita, and manembahKeywords: Character, Education, Wedatama.